Assessment of a Low-Cost Ultrasound Pericardiocentesis Model - Campo dell'Orto, Marco; Hempel, Dorothea; Starzetz, Agnieszka; Seibel, Armin; Hannemann, Ulf; Walcher, Felix; Breitkreutz, Raoul (Emergency Medicine International, 2013)
Introduction. The use of ultrasound during resuscitation is emphasized in the latest European resuscitation council guidelines of 2013 to identify treatable conditions such as pericardial tamponade. The recommended standard treatment of tamponade in various guidelines is pericardiocentesis. As ultrasound guidance lowers the complication rates and increases the patient’s safety, pericardiocentesis should be performed under ultrasound guidance. Acute care physicians actually need to train emergency pericardiocentesis. Methods. We describe in detail a pericardiocentesis ultrasound model, using materials at a cost of about 60 euros. During training courses of focused echocardiography n=67, participants tested the phantom and completed a 16-item questionnaire, assessing the model using a visual analogue scale (VAS). Results. Eleven of fourteen questions were answered with a mean VAS score higher than 60% and thus regarded as showing the strengths of the model. Unrealistically outer appearance and heart shape were rated as weakness of the model. A total mean VAS score of all questions of 63% showed that participants gained confidence for further interventions. Conclusions. Our low-cost pericardiocentesis model, which can be easily constructed, may serve as an effective training tool of ultrasound-guided pericardiocentesis for acute and critical care physicians.